(untitled) (Journal of Organizational Psychology, 2017)
Two studies sought to examine effects of gender and aggression on job performance ratings. Specifically, it was thought that negative performance episodes, such as aggressive behavior, might have less of an effect on performance ratings for males compared to females because males have a stereotype of being more aggressive. This hypothesis was tested in two studies: one with college undergraduate students and one with working adults. Results in both indicated that gender does not make a difference in performance ratings of aggressive behavior at work, suggesting that there may be less potential for discrimination in the evaluation of aggressive behavior.